Sorry for the delay in responding to this. I've been skipping over much stuff posted on vortex of late due to lack of time.

On Dec 19, 2007, at 8:57 AM, Stephen A. Lawrence wrote (in the WAY_OT: "The Mindless crap shoot of evolution" thread):


Something I encountered with surprise when I first studied logic is that the primary rule of inference:

   (A => B) & A   => B

is an assumption, not a theorem.

This depends on the definition of A => B. As used in the above assertion, (A=>B) has a truth value, otherwise the operation "&" is not closed. Thus A=>B can be defined as a function:

(A=>B)  ==  f(A,B)

where f(A,B) can be defined by:

A,  B, f(A,B)

F, F, T
F, T, T
T, F, F
T, T, T

It is then pretty easy to demonstrate, by substitution, the theorem with the table:

A,  B, f(A,B), [f(A,B) & A], f([f(A,B) & A],B)

F, F, T, F, T
F, T, T, F, T
T, F, F, F, F
T, T, T, T, T

From the right hand column we have by substitution in the equivalence definition, which works in either direction:

f([f(A,B) & A],B)  ==  [f(A,B) & A] => B

and then substituting the defined f(A,B) == (A=>B) we have:

(A=>B) & A => B

Q.E.D.

Horace Heffner
http://www.mtaonline.net/~hheffner/



Reply via email to